(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Tsisaruk V. State and structure of teachers’ technology readiness to learn the art school art wood processing. In the article a ready of teachers of technologies condition is determined to the studies of schoolchildren in industry of artistic treatment of wood and the structure of this readiness is grounded. Тhe level of readiness of teachers is tested and described ingeneral lines educational schools of the Lviv and Ternopil areas.